Assessment of Bamboo Forest Ecosystem Services in Thanh Hoa Province, Viet Nam - Dang, T.T.; Trinh, T.L.; Li, Y.; Jayaraman, D. (International Bamboo and Rattan Organisation (INBAR), 2020)
Thanh Hoa is a province in the north-central region of Viet Nam. The bamboo forest area covers 180,786 ha, accounting for 16.3% of the total natural land area. There have been few attempts to assess the type and extent of ecosystem services (ES) provided by the bamboo forests in Thanh Hoa province. This study attempts to evaluate ES for several types of land use. They include the Luong bamboo plantation (Dendrocalamus barbatus), a natural timber forest, an Acacia mangium plantation, paddy rice farming, maise farming and cassava farming.